Rhizoctonia solani, a seed-borne pathogen of French Bean in Malaysia - Wan Nik, Wan Zainun; Yap, M. Y (1979)
A study on some aspects of the biology, pathogenicity and control of Rhizcotonia solani Kuhn (the imperfect state of Thanatephorus cucumaris (Frank) Donk was undertaken using an isolate from infected French bean seed. The fungus was found to be seed-borne on both the imported and some local varieties of French bean. The rate of growth of the fungus varied with temperature and the medium used. Malt extract agar gave poor growth and lima bean agar supported the best growth of the fungus at 28°C. The fungus infects the aerial parts of the French bean plant. The strain was found to have a wide host range. An in vitro study to test the efficacy of fungicides against Rhizoctonia showed that pentachloronitrobenzene at 50 ppm gave a good control.